Intellectual Structure of Coronavirus Research: A Perspective From an Author Cocitation Analysis - Mei, Junyi; Zhao, Dangzhi; Strotmann, Andreas (Frontiers in Research Metrics and Analytics, 2020)
The present study examines the intellectual structure of research on coronavirus as revealed from an author co-citation analysis using citation data retrieved from the Web of Science Core Collection and mapped to the PubMed database. Four major dimensions are identified: (I) Outbreaks, (II) Viral structure and function, (III) Vaccine and therapeutic development, and (IV) Coronaviruses found in a range of animals. The “Outbreaks” dimension is by far the most prominent, dominated by reports on the three recent major outbreaks: COVID-19, SARS, and MERS. The focus of research on major outbreaks is on public health issues such as diagnosis, transmission, and clinical course. Research did not, however, stand out as a specialty or identifiable topic in the coronavirus research landscape identified here in a number of important areas, such as issues in mental health related to outbreaks. Results from this study should contribute to the understanding of the coronavirus research landscape and to the identification of strengths and weaknesses of current research on COVID-19.